Effect of herbal medical plants on anxiety: a brief review (Research, Society and Development, 2020)
Anxiety is one of the most common symptoms associated with the modern lifestyle. In contrast, there is an increase in the search for integrative and complementary practices such as herbal medicine to alleviate the symptoms associated with anxiety. Thus, this article aims to list the most used herbal medicines in the treatment of anxiety. This is a literature review of the last 18 years, where it was researched about the functioning and application of herbal medicines and their beneficial effects for health promotion, especially in anxiety. Carminative herbal remedies include valerian (Valeriana officinalis), mint (Mentha) and chamomile (Matricaria chamomilla), orange blossom (Citrus X sinensis), lemon balm (Melissa officinalis) and lemongrass (Cymbopogoncitratus). acute pains and sedatives, including passion fruit (Passiflora edulis), and in cases of insomnia include also white hawthorn (Crataeguslaevigata), and hops (Humuluslupulus). In relation to bioactive compounds, the use of fermented foods, essential oils - especially omega 3 flavonoids, have been shown to be potential alternative treatments for anxiety.